The Effectiveness of Concrete-Pictorial-Abstract Learning Strategy in Teaching Mixtures of Science Subjects to Students with Intellectual Skills Disabilities - Hasan Hüseyin Yıldırım; Havva Aysun Karabulut (Mimbar Sekolah Dasar, 2023)
The aim of this research is to examine the effectiveness of the concrete-pictorial-abstract teaching strategy presented with the direct teaching method in teaching the subject of mixtures, which is one of the science subjects, to students with intellectual disabilities. The study used multiple-probe model with a probe phase, one of the single-subject research models. While the dependent variable of the research was the level of showing the mixtures of the students participating in the study; the independent variable is the concrete-pictorial-abstract teaching strategy presented with the direct teaching method. The research was conducted with two girls and one boy living in Bolu, diagnosed with intellectual disability, and attending primary school. The data collected in the study were analyzed through visual analysis. As a result of the research, it has been observed that the concrete-pictorial-abstract learning strategy is effective in teaching the subject of mixtures to students with intellectual disabilities, that the permanence of this subject learned by the students can be maintained one and three weeks after the end of the education, and that all students can generalize this learning to different environments and tools.